1978
DOI: 10.1113/jphysiol.1978.sp012248
|View full text |Cite
|
Sign up to set email alerts
|

The sacral parasympathetic reflex pathway regulating colonic motility and defaecation in the cat.

Abstract: SUMMARY1. The sacral parasympathetic outflow to the large intestine of the cat was studied by monitoring simultaneously intestinal motility and the efferent firing in postganglionic fibres on the serosal surface of the mid-distal colon.2. Increases in efferent firing were noted during the occurrence of spontaneous propulsive activity (tonic pressure waves) or segmental contractions (slow rhythmic pressure waves). The neural discharge was not altered by transaction of the lumbar sympathetic innervation to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(66 citation statements)
references
References 27 publications
1
64
0
1
Order By: Relevance
“…This observation supports our statement that the inhibitory responses were the result of SCS modulating spinal neuronal activity and did not result from a change in colonic compliance. It has been shown that directly stimulating pelvic nerve afferent nerves from the colon with a high intensity and low frequency (12 V with trains of stimuli at 1.5 c/s, 4 shocks at 100 c/s and 0.05 msec duration) produce strong propulsive contractions of the colon (De Groat and Krier 1978). In the present studies, the stimulus intensity was much lower.…”
Section: Limitationsmentioning
confidence: 51%
“…This observation supports our statement that the inhibitory responses were the result of SCS modulating spinal neuronal activity and did not result from a change in colonic compliance. It has been shown that directly stimulating pelvic nerve afferent nerves from the colon with a high intensity and low frequency (12 V with trains of stimuli at 1.5 c/s, 4 shocks at 100 c/s and 0.05 msec duration) produce strong propulsive contractions of the colon (De Groat and Krier 1978). In the present studies, the stimulus intensity was much lower.…”
Section: Limitationsmentioning
confidence: 51%
“…18 Similarly, pelvic and/or sacral afferent fibres run in parallel to sacral parasympathetic outflow and are intimately connected by synapses in the spinal cord. 19 The anatomical sharing of peripheral nerve trunks by efferents and primary afferents is not just parsimonious-it reflects important functional connectivity.…”
Section: Classes Of Extrinsic Afferent Neuronsmentioning
confidence: 99%
“…Low levels of distension of the rectum activate rectal contractions and anal relaxations; 48 largely via sacral parasympathetic pathways. 19 Rectal distension in humans evokes sensations of urge at low pressures, unpleasantness at high pressures and pain at still higher pressures. 149 Pain and unpleasantness co-vary more closely than either sensation with urge.…”
Section: Extrinsic Afferent Pathways and Sensationmentioning
confidence: 99%
“…17 It is able to organise defecation even after upper spinal cord section. 19 However the sacral parasympathetic centre is also in¯uenced by supraspinal nervous structures. In the dog, the ®ring of sacral parasympathetic neurons is modulated by the pontine reticular formation.…”
Section: Extrinsic Parasympathetic Re¯exesmentioning
confidence: 99%